2015
DOI: 10.4172/2157-2518.1000237
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Serum Cea as a Predictive Biomarker for the Response to Neoadjuvant Chemoradiotherapy: A Meta-Analysis in Rectal Cancer

Abstract: Background: It is important to predict patients with rectal cancer responding well to neoadjuvant chemoradiotherapy (nCRT). Numerous studies have yielded inconsistent results regarding the relationship between pretreatment CEA level and the response to nCRT in patients with rectal cancer. We conducted a systematic review and meta-analysis of these studies to define the relationship between them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(55 reference statements)
0
1
0
Order By: Relevance
“… 31 Another meta-analysis evaluated the role of pretreatment CEA level and concluded that a normal level of CEA predicted more pCR. 32 The present study nevertheless kept one variable as a constant, as the interval to surgery was at a mean of 45 days with an SD of 3 days. The current study suggests that the independent predictive factor to achieve pCR is the pretreatment CEA level when surgery is performed at a mean interval of 45 days.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Another meta-analysis evaluated the role of pretreatment CEA level and concluded that a normal level of CEA predicted more pCR. 32 The present study nevertheless kept one variable as a constant, as the interval to surgery was at a mean of 45 days with an SD of 3 days. The current study suggests that the independent predictive factor to achieve pCR is the pretreatment CEA level when surgery is performed at a mean interval of 45 days.…”
Section: Discussionmentioning
confidence: 99%